2001
DOI: 10.1212/wnl.57.10.1916
|View full text |Cite
|
Sign up to set email alerts
|

No reversion in vigabatrin-associated visual field defects

Abstract: Sixty adult patients with partial epilepsy who have been treated with vigabatrin for 7 months to 14 years as mono- or add-on therapy were examined with repeated kinetic Goldmann perimetries to evaluate the prevalence, risk factors, and long-term outcome of vigabatrin-associated visual field defects. A follow-up examination was performed after 4 to 38 months (mean, 15 +/- 7) in 55 patients, 29 of whom had discontinued vigabatrin therapy. Neither reversion nor progression in visual field constriction was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 8 publications
5
47
0
1
Order By: Relevance
“…The visual field defects caused by vigabatrin seem to be permanent [67]. Retinal damage, assessed by electroretinogram (ERG), can be seen as soon as 2-3 months following vigabatrin initiation [32].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…The visual field defects caused by vigabatrin seem to be permanent [67]. Retinal damage, assessed by electroretinogram (ERG), can be seen as soon as 2-3 months following vigabatrin initiation [32].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…Men appear to be affected more than women (Hardus et al, 2001), while visual function has been reported to remain stable in patients who continue long-term therapy (Paul et al, 2001b). Finally, it remains unclear whether these VFDs are reversible (Vanhatalo et al, 2001) or not (Nousiainen et al, 2001).…”
Section: Completersmentioning
confidence: 99%
“…1,2 Since 1997 there have been numerous reports of concentric and/or binasal visual field defects associated with the use of Vigabatrin making this the most concerning safety issue with the use of the drug at present. [3][4][5][6] Previous studies have confirmed the high prevalence of visual field defects (up to 30-40%) and the lack of evidence for significant progression or resolution of these defects on cessation of the drug. 3,7,8 To date, there is little information with regard to the natural history of visual field defects in patients who continue on Vigabatrin.…”
Section: Introductionmentioning
confidence: 96%
“…[3][4][5][6] Previous studies have confirmed the high prevalence of visual field defects (up to 30-40%) and the lack of evidence for significant progression or resolution of these defects on cessation of the drug. 3,7,8 To date, there is little information with regard to the natural history of visual field defects in patients who continue on Vigabatrin. 3,9 Our study aimed to look at the natural history of visual field defects in a group of patients with known Vigabatrin-associated field loss who opted to continue on the drug because of good seizure control and consequent improvement in quality of life.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation